Potret Full Daycare sebagai Solusi Pengasuhan Anak bagi Orang Tua Perkerja: Studi pada TPA Pertiwi Metro - Hamer, Wellfarina; Rachman, Tubagus Ali; Lisdiana, Anita; Wardani, Wardani; Karsiwan, Karsiwan; Purwasih, Atik (Tapis: Jurnal Penelitian Ilmiah, 2020)
Children are priceless gifts, a great mandate that God entrusts to every parent. Parenting and environments greatly affect emotional-social intelligence and children's character. For working parents, efforts to meet the needs of children certainly have not been done optimally. For this reason, there are alternatives for working parents to continue to be able to provide rights and fulfillment of children's needs, namely by utilizing full daycare services where children are kept for a full day at the TPA (Child Care Park) until the parents have finished working. This study aims to describe the implementation of full daycare in one of the TPAs ​​in Metro City. How is the implementation of the landfill in terms of caring programs, education, nutrition, and health? Moreover, human resources were to be being a problem. The subject of this research is the TPA Pertiwi Metro. The method used in this research is descriptive qualitative. Data collection techniques using interviews, observation, and documentation on the principal, teachers, and parents of students. Data validity is done by triangulation of sources. From this research, it is known that TPA Pertiwi Metro excels in creating healthy, child-friendly, character-based, environmentally-based religious faith and diversity so that children still get a good education even though their parents work.